PENERAPAN MODEL PROBLEM BASED LEARNING(PBL) BERBANTUAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SDN 2 JAAR - Ina Agustin; Noniati (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
The aim of this research is to describe the improvement in student learning outcomes after implementing the Problem Based Learning learning model assisted by audiovisual media. This research was conducted at SDN 2 Jaar Kec. East Hamlet, Kab. East Barito. The subjects of this research were students in class VI SD Semester 1 2023/2024 with a total of 11 students. The research instrument used test sheets, teacher activity observation sheets in carrying out learning, student activity observation sheets and documentation. Data analysis was carried out using qualitative and quantitative descriptions. The results of the research show that the application of the Problem Based Learning Model assisted by audiovisual media to improve the Mathematics Learning Outcomes of Class VI Students at SDN 2 Jaar can improve the learning outcomes of class VI students at SDN 2 Jaar. In the pre-cycle, the average student achieved completeness in Mathematics with 6 students achieving a learning completion percentage of 55%. Meanwhile, after cycles I and II, the average student experienced an increase in Mathematics lesson completeness with students achieving learning completeness of 73% in Cycle I and 91% in Cycle II. From the data above it is known that the average student score has increased from pre-cycle 80.5 to 81 and 88.6 in cycles I and II respectively.